2019
DOI: 10.1021/acs.jafc.9b02668
|View full text |Cite
|
Sign up to set email alerts
|

Benzyl Isothiocyanate and Phenethyl Isothiocyanate Inhibit Adipogenesis and Hepatosteatosis in Mice with Obesity Induced by a High-Fat Diet

Abstract: Benzyl isothiocyanate (BITC) and phenethyl isothiocyanate (PEITC) are organosulfur phytochemicals rich in cruciferous vegetables. We investigated the antiobesity and antihepatosteatosis activities of BITC and PEITC and the working mechanisms involved. C57BL/6J mice were fed a low-fat diet (LFD), a high-fat diet (HFD), or a HFD supplemented with 0.5 (L) or 1 g/kg (H) BITC or PEITC for 18 weeks. Compared with the HFD group, BITC or PEITC decreased the final body weight of mice in a dose-dependent manner [39.0 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
(98 reference statements)
1
25
0
Order By: Relevance
“…However, Oil Red O staining indicated that different ITCs inhibited MDM-induced adipogenesis in different ways ( Figure 1B), even though they all had the N=C=S structure. Besides the N=C=S structure, the side chains of each ITC can also contribute to ITC bioactivity in terms of lipophilicity, side-chain length, molecular geometry, and chemical stability [27,55]. Given the results published in previous studies [56,57], our findings suggest that SFEN interacts with C/EBPβ at an earlier stage of adipogenesis than other ITCs ( Figure 1B).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…However, Oil Red O staining indicated that different ITCs inhibited MDM-induced adipogenesis in different ways ( Figure 1B), even though they all had the N=C=S structure. Besides the N=C=S structure, the side chains of each ITC can also contribute to ITC bioactivity in terms of lipophilicity, side-chain length, molecular geometry, and chemical stability [27,55]. Given the results published in previous studies [56,57], our findings suggest that SFEN interacts with C/EBPβ at an earlier stage of adipogenesis than other ITCs ( Figure 1B).…”
supporting
confidence: 66%
“…We compared the ability of SFEN to inhibit adipogenesis to those of other ITCs, including SFN, IBR, ERC, AITC, BITC, and PEITC. The anti-adipogenic effects of these ITCs have been described previously [25][26][27]32]. To investigate whether SFEN exerts the strongest inhibitory effect against MDM-induced adipogenesis among this group of ITCs, we tested the effects of multiple ITCs at the same concentration (10 µM) in the presence of MDM, an adipogenic inducer.…”
Section: Sfen Exhibits Stronger Anti-adipogenic Effects Than Other Itcsmentioning
confidence: 99%
See 1 more Smart Citation
“…BITC has been studied in various cancers, such as oral cancer [10], pancreatic cancer [11], brain cancer [12], melanoma [13,14], and gastric cancer [15], to evaluate its potential for cytotoxic effects on cancer cells. Additionally, BITC has been shown to have anthelmintic [16], anti-inflammatory [17], and anti-adipogenic effects [18]. Due to the large number of therapeutic advantages that have been found in various studies, BITC has gained interest as a novel therapeutic candidate for gastric cancer, with potential chemopreventive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Fat deposition decrease in WAT takes place through inhibition of C/EBPα and PPARγ and the suppression of lipogenesis via activation of the AMPKa pathway ( 268 ). In HFD fed mice, Chuang et al described that BITC and PEITC prevent body weight gain in a dose-dependent manner with diminishing adipogenesis and prevention of hepatosteatosis through inhibition of the lipogenic regulatory transcription factors PPARγ, LXRα, and SREBP1c, and a decrease in their regulated downstream enzymes ( 266 ). They also found that BITC and PEITC had similar effects and that 3T3-L1 cells were arrested in the G0/G1 phase.…”
Section: Metabolic Syndrome: Definitionmentioning
confidence: 99%